OPTIMIZATION THE PERFORMANCE OF THE CRIMNINAL INVESTIGATION UNIT IN THE SETTLEMENT OF THE CRIME OF STEALING TO INCREASE CRIME CLEARANCE AT SRAGEN POLICE REGION - MUHAMMAD DARMANSYAH (Advances in Police Science Research Journal, 2022)
The final project written by author discusses the optimization of the Sat Reskrim performance, especially members of the Resum I unit in resolving the crime of theft with weights in the jurisdiction of the Sragen Police. This is motivated by theft with weighting which is still a crime with a high crime rate compared to others. Therefore, the Sat Reskrim Polres Sragen seeks to optimize performance so that its implementation is in accordance with the Regulation of the Head of the Indonesian National Police Number 6 of 2019 concerning Criminal Investigations and Perkabareskrim Number 1 of 2014 concerning SOPs for Planning for Criminal Investigations. This study aims to: (1) describe the performance of the Criminal Investigation Unit in the settlement of the criminal act of Curat, (2) describe the efforts to optimize the performance of the Criminal Investigation Unit in the settlement of the crime of stealing. In the conceptual literature to analyze the problems above, several theories are used in the research, namely; Management theory, and Performance Theory. While the concept used is the concept of Optimization, the concept of Theft by Weighting. This type of research uses field research and a qualitative approach. Data collection techniques used are interviews, observation and document research. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of the study found that there were still obstacles, namely the lack of members of the Sat Reskrim Polres Sragen making it difficult to resolve criminal cases due to the large number of criminal cases that occurred. Lack of public knowledge of the importance of crime scenes, many damaged crime scenes. The conclusions in this final project, (1) The Sat Reskrim's performance is still not optimal, it must be adjusted to Perkap No. 6 of 2019. (2) Efforts to optimize performance are still not carried out properly, but evaluations must still be carried out to control the performance of members.